Key technologies of visible light communications with multiple LEDs - Fubin WANG; Shiyuan SUN; Menghui WANG; Fang YANG; Xiaofei WANG; Jian SONG (Dianxin kexue)
Visible light communication (VLC), primarily based on light emitting diode (LED), supports the information transmission and networking through the existing infrastructure of the illumination network.The constellation optimization and the power resource optimization were investigated under lighting constraints with multiple LEDs for indoor environment.Moreover, the optical intelligent reflection surface was also researched to regulate reflection channels dynamically, improving both the transmission data rate and the coverage of the VLC system.In the meantime, the preliminary study revealed the flicker effect of low-frequency modulated optical signals on the human body, and the results suggest that the LED photo-biological effect should be considered comprehensively in the future signal design.